Quy trình phát triển chương trình giáo dục phổ thông Việt Nam từ góc nhìn so sánh - Đỗ, Ngọc Thông (Viện KHGD Việt Nam, 2020)
This article looks at the school curriculum development process in Vietnam from the comparative view with other countries. The author addresses: 1/the need for comparative school education, 21 international comparisons of school education, 3/school curriculum development process, 4/ discrepancies in Vietnam's school curriculum development as compared to other countries.